Review paper Modern methods of conservative treatment of pressure ulcers - Sopata, Maciej; Tomaszewska, Elżbieta; Machyńska-Bućko, Zofia; Kotlińska-Lemieszek, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
This paper presents a modern concept of conservative treatment of pressure ulcers in the moist environment. Dressing types, their characteristics and a system of “colour” wound classification are presented.